2018
DOI: 10.1016/j.bja.2017.11.083
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic efficacy of bilateral superficial cervical plexus block for thyroid surgery: meta-analysis and systematic review

Abstract: BSCPB offers analgesic efficacy in the early postoperative period for up to 24 h after thyroid surgery, with reduced length of hospital stay, but without any beneficial effect on PONV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 26 publications
3
47
1
Order By: Relevance
“…Studies reported that the block allowed to reduce anesthetic requirements and provided prolonged postoperative analgesia. It also decreased pain score, rescue analgesic requirement and overall opioid requirement in the first 24 postoperative hours [12][13][14]. Hence, it minimizes opioids related adverse outcomes and cost [15].…”
Section: Introductionmentioning
confidence: 99%
“…Studies reported that the block allowed to reduce anesthetic requirements and provided prolonged postoperative analgesia. It also decreased pain score, rescue analgesic requirement and overall opioid requirement in the first 24 postoperative hours [12][13][14]. Hence, it minimizes opioids related adverse outcomes and cost [15].…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that this comprehensive strategy was safe and associated with a very high rate of patient satisfaction. Other studies have demonstrated the efficacy of other adjuvant analgesic strategies such as superficial nerve blocks, perioperative neuroleptics, and preoperative and postoperative combinations of APAP and NSAIDs . Notably among our cohort, the reported use of non‐opioid pain management was quite common with over 85% of those surveyed employing at least one strategy.…”
Section: Discussionmentioning
confidence: 74%
“…Multiple studies have investigated the effectiveness of BSCPB in thyroid surgery and reported that it was effective in minimizing pain scores, opioid and total analgesic consumption and prolonging analgesia duration [12,13,20,21]. A meta-analysis of 14 studies incorporated 1154 patients revealed BSCPB significantly reduced analgesic requirement, VAS scores and lengthen time to first analgesic request [14]. BSCPB was found significantly associated with nearly half shorter postoperative hospital stay (2.4 ± 0.6 vs 4.7 ± 1.6; p < 0.05) [12].…”
Section: Discussionmentioning
confidence: 99%
“…Performing regional nerve blocks and administration of multi-modal analgesics prior to surgical incision are helpful in reducing intra-and postoperative opioid consumption, primary hyperalgesia, central sensitization and chronic pain [14,22,26]. In combination with gabapentin, BSCPB has prevented delayed neuropathic pain at 6 th postoperative month [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation